An evaluation method of supercritical CO2 thickening result for particle transporting. (October 2017) - Hou, Lei; Jiang, Tingxue; Liu, He; Geng, Xueyu; Sun, Baojiang; Li, Gensheng; Meng, Siwei
Graphical abstract: Highlights: Visualization experiments of particle-SC CO2 two-phase flow have been performed. A new evaluation method of SCCO2 thickening result has been proposed. There is an optimum value of enhanced supercritical CO2 viscosity. The particle settling velocity determines the transporting capability of SCCO2 . Abstract: This paper aims to propose an evaluation method for measuring the supercritical CO2 thickening result for particle transporting. By analyzing the particle transporting trajectory in supercritical CO2, the cotangent of particle landing angle (ratio of particle horizontal velocity to vertical velocity) was proposed as a new criterion of thickening result. Previous studies of supercritical CO2 thickening were evaluated and drawn in three dimensions using this new criterion. Moreover, the effects of CO2 density and viscosity on particle vertical and horizontal velocities and the cotangent of particle landing angle were analyzed. The cotangent of particle landing angle is more sensitive to supercritical CO2 density than viscosity. Therefore, supercritical CO2 density should be considered for the evaluation of supercritical CO2 thickening for particle transporting. The particle settling velocity was found to determine the particle transporting distance and also the transporting capability of supercritical CO2 . According to this conclusion, the apparatus for experimental evaluation of supercritical CO2 thickening will be miniaturized significantly by the simplification from two-dimensional velocities measurement into one direction, particle settling velocity in vertical direction. Additionally, the supercritical CO2 viscosity was found to have an optimum value, exceeding which the effect of viscosity on particle transporting levels off.